Interreligious Marriage in Indonesia and Malaysia: Strict and Loose Legal Policy - Imaduddin, Zhorif Agung; Putranti, Deslaely; Marwa, Muhammad Habibi Miftakhul (Al-Ahwal: Jurnal Hukum Keluarga Islam, 2024)
In practice, marriages do not always occur between individuals of the same religious background. Interfaith marriages take place when partners of different religions marry without requiring one partner to convert. This study aims to examine the legal issues surrounding interfaith marriages in Indonesia and Malaysia through a comparative analysis. It adopts a normative legal research methodology, incorporating both comparative and case-based approaches. Data were obtained from literature and other secondary sources. The findings indicate that Indonesian marriage law does not explicitly regulate interfaith marriages, and the Law on Population Administration does not require that registered marriages be between individuals of the same religion. In contrast, Malaysian law strictly prohibits interfaith marriages, and any violation results in the annulment of the marriage's legal status. [Dalam praktiknya, perkawinan tidak hanya terjadi antara pemeluk agama yang sama. Perkawinan beda agama terjadi ketika pasangan yang berbeda agama menikah tanpa mengharuskan salah satu pasangannya berpindah agama. Penelitian in ibertujuan untuk mengetahui permasalahan hukum pada perkawinan beda agama di Indonesia dan Malaysia secara komparatif. Penelitian ini merupakan penelitian hukum normative dengan pendekatan komparatif dan pendekatan kasus. Data dalam penelitian ini diperoleh melalui literatur atau data sekunder. Hasil dari penelitian ini menunjukkan bahwa UU Perkawinan di Indonesia tidak secara tegas mengatur perkawinan beda agama, dan dalam UU Administrasi Kependudukan, tidak ada ketentuan yang mengatur mengenai perkawinan yang dicatatkan harus menganut agama yang sama. Sedangkan di Malaysia, pernikahan beda agama dilarang keras dalam Hukum Malaysia. Pelanggaran atas ketentuan ini akan mengakibatkan penolakan pengesahan perkawinan.]